Key and checklist of Xanthophyllum (Polygalaceae) of Borneo - De Wilde, W.J.J.O.; Duyfjes, Brigitta E.E. (Research Center for Biology, 2009)
A key to and a check list of the 56 Xanthophyllum (Polygalaceae) species of Borneo is presented. One species is newly described, X. albicaulis. Xanthophyllum hildebrandii is sunk in X. ellipticum.